1982
DOI: 10.1038/clpt.1982.91
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cimetidine on caffeine disposition in smokers and nonsmokers

Abstract: The absorption, distribution, and elimination of caffeine, 2 mg/kg by mouth, were evaluated in six smokers and six nonsmokers before and on the fourth day of administration of cimetidine, 300 mg by mouth every 6 hr. Caffeine absorption, assessed by the maximal serum caffeine concentration (C max) and the time to reach Cmax (t max), was very rapid relative to elimination. The total body clearance (TBC) of caffeine was higher (2.49 +/- 0.35 and 1.59 +/- 0.19 ml/kg/min, P less than 0.05) and the elimination half-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(18 citation statements)
references
References 0 publications
1
16
1
Order By: Relevance
“…It is also interesting that caffeine is detected in habitual caffeine-consuming humans at concentrations capable of antagonizing A2AR, 10 -50 M in moderate to heavy caffeine consumers (43,44). Other studies showed that when humans acutely ingested 2-2.5 mg/kg caffeine (corresponding to the amount in two cups of coffee), blood caffeine concentration was ϳ20 M (41,45,46). In contrast, amounts of caffeine much higher than what people usually consume will be required for the immunosuppressive effects of caffeine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also interesting that caffeine is detected in habitual caffeine-consuming humans at concentrations capable of antagonizing A2AR, 10 -50 M in moderate to heavy caffeine consumers (43,44). Other studies showed that when humans acutely ingested 2-2.5 mg/kg caffeine (corresponding to the amount in two cups of coffee), blood caffeine concentration was ϳ20 M (41,45,46). In contrast, amounts of caffeine much higher than what people usually consume will be required for the immunosuppressive effects of caffeine.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the same per kilogram dose of caffeine does not reproduce the same blood concentration in humans and mice. Indeed, the serum caffeine concentration after a dose of 2 mg/kg was 10 M in mice while it was 25 M in humans (41,42). Considering such differences, it is suggested that 10 mg/kg of caffeine in rodents represents 3.5 mg/kg in humans, which corresponds to 2-3 cups of coffee for a 70-kg human (1).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have shown that caffeine can enhance the reinforcing effects of nicotine (Shoaib et al, 1999;Jones and Griffiths, 2003), no study has evaluated whether nicotine enhances the reinforcing effects of caffeine. However, it is known that cigarette smoking decreases the half-life of caffeine by as much as 50% (Parsons and Neims, 1978;May et al, 1982). Thus, higher rates of caffeine consumption among cigarette smokers may be due to the faster rate of caffeine elimination.…”
Section: Effects Of Nicotine Maintenance On Intravenous Caffeinementioning
confidence: 99%
“…Interestingly, the inhibitory effect of erythromycin is greatest in subjects who clear warfarin relatively slowly. May et al [13] reported a similar inverse relationship for cimetidine's inhibitory effect on caffeine elimination, noting that the greatest impair ment of caffeine elimination by cimetidine occurs in individuals whose elimination is initially slow.…”
Section: Discussionmentioning
confidence: 71%